Determinan Sosial Ekonomi Kepemilikan Jaminan Kecelakaan Kerja pada Tenaga Kerja Informal di Indonesia: Analisis Data SUSENAS 2017 - Madya, Sri Denti On; Nurwahyuni, Atik (UI Scholars Hub, 2018)
The number of informal workers is higher than the formal workforce in Indonesia. The coverage of working accident protection is still very low while the work accident rate still tends to be high. This study aims to determine the socio-economic determinants of employ ment accident insurance ownership in informal workers in Indonesia. This study used a cross sectional study design with bivariate analysis using the estimation method of maximum likelihood. The Susenas Data (National Socio-Economic Survey) in 2017 is ana lyzed using logistic/logit regression. The variables observed were age, sex, marital status, health, education, regional complaints, and socio-economic/informal labor income. The results of the study indicated a relationship between region (p=0,0005), age (p=0,0005), sex (p=0,0005), marital status (p=0,001), education (p=0,0005), and socio-economic/income (p=0,0005) in informal labor on em ployement accident insurance ownership in Indonesia. The econometric model show that the factors that most influence the owner ship of work accident insurance in the informal sector workforce are informal labor characteristics consisting of education (OR 1.94), Age (OR 1.09), region (OR 1.71), and income (OR 1.79).